Case report: Induction and maintenance of steroid-free remission with vedolizumab in a case of steroid-dependent autoimmune pancreatitis - Griebel, Paul; Tran, Florian; Luehring, Janina; Schreiber, Stefan (Frontiers in Immunology, 2023)
Type 2 autoimmune pancreatitis responds well to corticosteroids in most instances. Additional immunosuppression or low-dose maintenance steroids may be necessary upon relapse. There is limited data on alternative strategies when these regiments fail or cause adverse reactions. We report a case of a middle-aged woman with type 2 autoimmune pancreatitis in whom tapering of prednisolone below the dose of 25mg per day resulted in relapse of symptoms and long-term steroid use led to development of steroid induced hyperglycaemia. Induction and maintenance of steroid-free remission was ultimately successful under vedolizumab therapy. Remission has been stable for over one year with reduced need for antidiabetic intervention. This is the first reported case of treatment of refractory autoimmune pancreatitis with vedolizumab. It highlights the overlap of immunological mechanisms within inflammatory diseases of the digestive tract and how knowledge of biological data can inform treatment decisions for individual cases. The demonstrated efficacy of vedolizumab and low risk of severe side warrant further investigation into its use in autoimmune pancreatitis.